Biochar-driven cycling of Fe(II)/Fe(III) and Co(II)/Co(III) in cobalt ferrite for efficient norfloxacin degradation via Fenton-like pathway - Rui Gan; Fanguang Kong; Xiao Zhao; Daoqing Liu; Shuo Zhang; Wen Liu; Si Li; Weiling Sun (Chemical Engineering Journal, 2026)

Multidimensional nontarget screening reveals the hidden complexity of emerging contaminants from influents to effluents in drinking water treatment plants - Yitao Lyu; Dantong Jia; Tingting Zhu; Bei Wang; Moran Tang; Tianchang Huang; Xu Nan; Weiling Sun (Water Research, 2026)

Nontarget screening uncovers the overlooked impact of antibiotic transformation products on riverine resistomes - Yiming Feng; Xuman Zhang; Shanshan Lai; Fan Chen; Jingrun Hu; Min Li; Weiling Sun (Journal of Hazardous Materials, 2026)

Construction of a comprehensive water quality assessment framework integrating abiotic indicators, multi-taxonomic biological communities, and machine learning - Tianyi Chen; Qian Chen; Xinzong Xiao; Xuefeng Guo; Fang Guo; Xinyong Liu; Yitao Lv; Nan Xu; Weiling Sun (Journal of Hydrology, 2026)

Genomic blueprint enables early intervention in cyanobacterial risk management - Jiawen Wang; Ying Chen; Tianyi Chen; Hetong Cai; Qian Chen; Weiling Sun; Jinren Ni (Science Bulletin, 2025)

Integrated wide-scope and class-specific nontarget analysis reveals a broad spectrum of organic micropollutants in an urban river - Jingrun Hu; Yi Liu; Xuman Zhang; Zhuoyu Chen; Moran Tang; Yitao Lyu; Xiuqi You; Damian E. Helbling; Weiling Sun (Water Research, 2025)

Beyond top-hit nontarget screening: Diagnostic fragment analysis reveals nitrogen-containing heterocycles in iron and steel industry wastewater - Yi Liu; Quanxi Zhang; Yuru Guo; Jingrun Hu; Rongkui Su; Chao Yao; Weiling Sun (Journal of Hazardous Materials, 2025)

A clustering approach based on high-resolution ecological vulnerability index reveals spatial patterns of per- and polyfluoroalkyl substances pollution in lakes on the Tibetan Plateau - Xu Han; Baozhu Pan; Zhile Pan; Nan Xu; Jiang Wu; Weiling Sun; Bowen Hou; Yanran Dong (Water Research, 2025)

Mediating Zn loading on Cu-Zn bimetallic catalyst for electrochemical CO2 reduction into tunable syngas - Yafei Guo; Yangna Luo; Hanlin Wang; Xianglin Chen; Xiang Liu; Benshuai Guo; Jian Sun; Ruilin Wang; Weiling Li; Chuanwen Zhao (Fuel, 2025)

Unveiling the mechanism and driving factors of pharmaceutical and personal care product (PPCP) removal in wastewater treatment plants - Shaoyang Li; Zhen Gao; Tianyi Chen; Zhile Pan; Dianbao Li; Yanran Dong; Junjie Li; Yanli Zhang; Sihan Cui; Weiling Sun; Nan Xu (Journal of Environmental Management, 2025)

Biochar application for enhancing water and nitrogen use efficiency of understory acacia species in a suburban native forest subjected to nitrogen deposition in Southeast Queensland - Weiling Sun; Yinan Li; Zhihong Xu; Yifan Bai; Shahla Hosseini Bai (Plant and Soil, 2024)
Purpose The fuel reduction prescribed burning and biochar application can have significant impacts on water and nitrogen (N) use efficiency of understory acacia species as well as soil carbon (C) and N pools in a suburban native forest subject to N deposition in Southeast Queensland, Australia. Methods We evaluated the impact of biochar application rates (0, 5.0 and 10.0 t biochar per hectare) and prescribed burning on soil-plant interactions in carbon (C) and N cycling in a suburban native forest in the first two years of biochar application or three and half years of the recently prescribed burning. Results Anthropogenic N deposition not only enhanced N losses caused by N leaching and denitrification, but also inhibited biological N fixation (BNF) by increasing N availability in forest systems. The Acacia leiocalyx with higher water use efficiency was more inclined to utilize easily available N resources (from N deposition), compared with A. disparismma . In this study, biochar application could indeed reduce N loss in forest soil and improve soil fertility by improving plant water and N use efficiency. Meanwhile, soil moisture content affected by biochar application also influenced soil N transformations by affecting soil microbial activity. Conclusion For urban forest soils, the high N availability caused by N deposition could inhibit the BNF in a suburban native forest ecosystem. The high-porosity physical structure of biochar applied increased the soil water content and soil N retention capacity.

Distribution and drivers of co−hosts of antibiotic and metal(loid) resistance genes in the fresh−brackish−saline groundwater - Xuming Xu; Huan Chen; Lei Du; Chunfang Deng; Ruoqi Ma; Bin Li; Jiarui Li; Shufeng Liu; Raghupathy Karthikeyan; Qian Chen; Weiling Sun (Chemosphere, 2024)

Enhancing and sustaining arsenic removal in a zerovalent iron-based magnetic flow-through water treatment system - Yuchen Wu; Yuyan Wang; Delai Zhong; Jinli Cui; Weiling Sun; Yi Jiang (Water Research, 2024)

Immunotoxicity of legacy and alternative per- and polyfluoroalkyl substances on zebrafish larvae - Dengdiao Yao; Jian Shao; Dantong Jia; Weiling Sun (Environmental Pollution, 2024)

Impacts of rapidly urbanizing watershed comprehensive management on per- and polyfluoroalkyl substances pollution: Based on PFAS “diversity” assessment - Nan Xu; Zhile Pan; Wenjing Guo; Shaoyang Li; Dianbao Li; Yanran Dong; Weiling Sun (Water Research, 2024)

Profiles, drivers, and prioritization of antibiotics in China’s major rivers - Yi Liu; Meng Zhang; Yang Wu; Si Li; Jingrun Hu; Weiling Sun; Jinren Ni (Journal of Hazardous Materials, 2024)

When antibiotics encounter microplastics in aquatic environments: Interaction, combined toxicity, and risk assessments - Yibo Zhang; Xin Xu; Jing Xu; Zhang Li; Long Cheng; Jie Fu; Weiling Sun; Chenyuan Dang (Science of The Total Environment, 2024)

Portable, intelligent MIECL sensing platform for ciprofloxacin detection using a fast convolutional neural networks-assisted Tb@Lu2O3 nanoemitter - Zhiwei Lu; Yonghui Gong; Chengao Shen; Haoran Chen; Weiling Zhu; Tao Liu; Chun Wu; Mengmeng Sun; Gehong Su; Xianxing Wang; Yanying Wang; Jianshan Ye; et al. (Food Chemistry, 2024)

Long-term effects of biochar application on biological nitrogen fixation of acacia species and soil carbon and nitrogen pools in an Australian subtropical native forest - Yinan Li; Weiling Sun; Zhihong Xu; Yifan Bai; Shahla Hosseini Bai (Journal of Soils and Sediments, 2024)
Purpose Biological nitrogen (N) fixation (BNF) of understory acacia species presents a potential way for effectively restoring N in forest systems. This study aimed to quantify the impact of acacia species and biochar application rates on BNF and soil mineral N in a suburban native forest of subtropical Australia in the first 4–5 years after prescribed burning. Method Plant growth values and BNF were measured to assess the impact of biochar rates at 0, 5, and 10 t ha −1 on different acacia species. Soil NH 4 + -N and NO 3 − -N along with their N isotope composition (δ 15 N) were determined to investigate soil–plant interactions in response to acacia species and biochar application. Results The application of 10 t ha −1 biochar significantly enhanced the growth of acacia species, and concurrently reduced the loss of NO 3 − -N at soil depths of 0–5 and 5–10 cm. Compared with Acacia disparimma (percentage of N derived from the atmosphere or %Ndfa: 78.2%), A. leiocalyx demonstrated significant higher BNF ability (%Ndfa: 91.3%). Similarly, A. leiocalyx had better growth, in terms of height (269.1 cm versus 179.6 cm), diameter at ground level (2.62 cm versus 1.94 cm), basal area (6.49 cm 2 versus 3.43 cm 2 ) and volume (692.2 cm 3 versus 258.0 cm 3 ). This was associated with its ability to promote organic matter mineralization, resulting in the accumulation of 15 N-depleted NH 4 + -N. NH 4 + -N, acting as a substrate, was transformed into NO 3 − -N through nitrification. From regression analysis, the efficient absorption of NH 4 + -N by A. leiocalyx significantly mitigated NH 4 + -N leaching with increasing soil moisture concentration (SMC), resulting in lower δ 15 N of NH 4 + -N, which was more negatively related to SMC (R 2 = 0.401), compared to that of A. disparimma (R 2 = 0.250) at soil depth of 0–5 cm. The production of NO 3 − -N was reduced, leading to lower NO 3 − -N concentrations of A. leiocalyx than A. disparimma at soil depth of 0–5 cm (8.06 µg N g −1 versus 9.61 µg N g −1 ) and that of 5–10 cm (8.24 µg N g −1 versus 9.21 µg N g −1 ) respectively. Conclusions As an effective soil amendment, biochar exhibited promise in reducing mineral N loss and stimulating plant growth in long-term applications of exceeding three years. Higher BNF capacity and greater plant growth were observed with A. leiocalyx , compared with those of A. disparimma . The retention and utilisation of mineral N by A. leiocalyx can be considered as strategy to restore forest soils.

CPR bacteria and DPANN archaea play pivotal roles in response of microbial community to antibiotic stress in groundwater - Moran Tang; Qian Chen; Haohui Zhong; Shufeng Liu; Weiling Sun (Water Research, 2024)

Planktonic/benthic Bathyarchaeota as a “gatekeeper” enhance archaeal nonrandom co-existence and deterministic assembling in the Yangtze River - Shufeng Liu; Yahsuan Lin; Tang Liu; Xuming Xu; Jiawen Wang; Qian Chen; Weiling Sun; Chenyuan Dang; Jinren Ni (Water Research, 2023)

Short-term changes in soil labile carbon and nitrogen pools with biochar application in a suburban native forest in subtropical Australia - Jiaping Yang; Juan Zhan; Sabah Taresh; Weiling Sun; Yinan Li; Ashrafun Nessa; Qinggui Wu; Zhihong Xu (Journal of Soils and Sediments, 2023)

Wastewater treatment plant effluents exert different impacts on antibiotic resistome in water and sediment of the receiving river: Metagenomic analysis and risk assessment - Yang Wu; Si Li; Ke Yu; Jingrun Hu; Qian Chen; Weiling Sun (Journal of Hazardous Materials, 2023)

Distinct adaptive strategies and microbial interactions of soil viruses under different metal(loid) contaminations - Zongzhi Wu; Pinggui Cai; Enhang Liang; Qian Chen; Weiling Sun; Jiawen Wang (Journal of Hazardous Materials, 2023)

Differential toxicity of various mineral nanoparticles to Synechocystis sp.: With and without ciprofloxacin - Xiuqi You; Xiaoqiang Cao; Xuan Zhang; Yi Liu; Weiling Sun (Journal of Hazardous Materials, 2023)

Enhancing H2O2 utilization efficiency for catalytic wet peroxide oxidation through the doping of La in the Fe-ZSM-5 Catalyst - Weiling Piao; Wenjing Sun; Danyang Yu; Wanying Zhang; Huangzhao Wei; Chenglin Sun (Environmental Science and Pollution Research, 2023)

Animal production predominantly contributes to antibiotic profiles in the Yangtze River - Jingrun Hu; Si Li; Wei Zhang; Damian E. Helbling; Nan Xu; Weiling Sun; Jinren Ni (Water Research, 2023)

Insights into the driving factors of vertical distribution of antibiotic resistance genes in long-term fertilized soils - Ying Li; Fanguang Kong; Si Li; Jie Wang; Jingrun Hu; Shuo Chen; Qing Chen; Yanming Li; Xuejiao Ha; Weiling Sun (Journal of Hazardous Materials, 2023)

Deciphering the dynamics of metal and antibiotic resistome profiles under different metal(loid) contamination levels - Pinggui Cai; Qian Chen; Wenran Du; Shanqing Yang; Jiarui Li; Hetong Cai; Xiaohui Zhao; Weiling Sun; Nan Xu; Jiawen Wang (Journal of Hazardous Materials, 2023)

Correlation of heavy metals’ exposure with the prevalence of coronary heart disease among US adults: findings of the US NHANES from 2003 to 2018 - Xi Li; Dongdong Zhang; Yang Zhao; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Environmental Geochemistry and Health, 2023)

Insights into the responses of fungal taxonomy and function to different metal(loid) contamination levels - Jiawen Wang; Ying Chen; Wenran Du; Shanqing Yang; Yifan He; Xiaohui Zhao; Weiling Sun; Qian Chen (Science of The Total Environment, 2023)

Air pollution exposure and heart failure: A systematic review and meta-analysis - Dongdong Zhang; Weiling Chen; Cheng Cheng; Hao Huang; Xi Li; Pei Qin; Chuanqi Chen; Xinping Luo; Ming Zhang; Jing Li; Xizhuo Sun; Yu Liu; et al. (Science of The Total Environment, 2023)

Reveal the major factors controlling quinolone adsorption on mesoporous carbon: Batch experiment, DFT calculation, MD simulation, and machine learning modeling - Hongjun Zhao; Yitao Lyu; Jingrun Hu; Min Li; Huan Chen; Yi Jiang; Moran Tang; Yang Wu; Weiling Sun (Chemical Engineering Journal, 2023)

Single and combined genotoxicity of metals and fluoroquinolones to zebrafish embryos at environmentally relevant concentrations - Dantong Jia; Xiuqi You; Moran Tang; Yitao Lyu; Jingrun Hu; Weiling Sun (Aquatic Toxicology, 2023)

Integration of target, suspect, and nontarget screening with risk modeling for per- and polyfluoroalkyl substances prioritization in surface waters - Jingrun Hu; Yitao Lyu; Huan Chen; Leilei Cai; Jie Li; Xiaoqiang Cao; Weiling Sun (Water Research, 2023)

Antibiotic profiles and their relationships with multitrophic aquatic communities in an urban river - Yitao Lyu; Xuming Xu; Yibin Yuan; Zhaoli Wang; Jingrun Hu; Qian Chen; Weiling Sun (Science of The Total Environment, 2023)

CuS quantum dots activated DNAzyme for ratiometric electrochemical detection of telomerase activity - Yujie Sun; Qi Dong; Huan Yang; Weiling Song; Hong Zhou (Analytica Chimica Acta, 2023)

Exploring diversity patterns and driving mechanisms of the antibiotic resistome and microbiome in saline groundwater - Moran Tang; Qian Chen; Haohui Zhong; Feng Ju; Yang Wu; Jingrun Hu; Si Li; Weiling Sun (Journal of Hazardous Materials, 2023)

Short-term responses of soil carbon and nitrogen pools as well as their isotopic compositions to biochar applications in a suburban forest in subtropical Australia subjected to prescribed burning - Jiaping Yang; Juan Zhan; Sabah Taresh; Ashrafun Nessa; Weiling Sun; Qinggui Wu; Zhihong Xu (Journal of Soils and Sediments, 2023)

Polybrominated diphenyl ethers in water, suspended particulate matter, and sediment of reservoirs and their tributaries in Shenzhen, a mega city in South China - Tingting Zhu; Youchang Zhu; Yunlang Liu; Chen Deng; Xiujuan Qi; Jinling Wang; Zhizhi Shen; Donggao Yin; Yihong Liu; Ruohan Sun; Weiling Sun; Nan Xu (Environmental Science and Pollution Research, 2023)

Insight into sulfamethoxazole effects on aerobic denitrification by strain Pseudomonas aeruginosa PCN-2: From simultaneous degradation performance to transcriptome analysis - Yuanyi Zhao; Hongchao Min; Kongyan Luo; Huan Chen; Qian Chen; Weiling Sun (Chemosphere, 2023)

Effectiveness and safety of vonoprazan-based regimens compared with those of proton pump inhibitor (PPI)–based regimens as first-line agents for Helicobacter pylori: a meta-analysis of randomized clinical trials - Yingchao Sun; Lei Yue; Weiling Hu (European Journal of Clinical Pharmacology, 2023)

Effect of inorganic salt on the removal of typical pollutants in wastewater by RuO2/TiO2 via catalytic wet air oxidation - Wanying Zhang; Wenjing Sun; Yanan Zhang; Danyang Yu; Weiling Piao; Huangzhao Wei; Xiaowei Liu; Chenglin Sun (Chemosphere, 2023)

Development of an interpretable machine learning model associated with heavy metals’ exposure to identify coronary heart disease among US adults via SHAP: Findings of the US NHANES from 2003 to 2018 - Xi Li; Yang Zhao; Dongdong Zhang; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Chemosphere, 2023)

Black carbon and humic acid alleviate the toxicity of antibiotics to a cyanobacterium Synechocystis sp. - Mingtao You; Xiuqi You; Xi Yang; Jingrun Hu; Yitao Lyu; Weiling Sun (Environmental Pollution, 2023)

Environmental DNA metabarcoding reveals the impacts of anthropogenic pollution on multitrophic aquatic communities across an urban river of western China - Xuming Xu; Yibin Yuan; Zhaoli Wang; Tong Zheng; Hetong Cai; Malan Yi; Tianhong Li; Zhijie Zhao; Qian Chen; Weiling Sun (Environmental Research, 2023)

Comparison and prioritization of antibiotics in a reservoir and its inflow rivers of Beijing, China - Jingrun Hu; Dianqing Qi; Qian Chen; Weiling Sun (Environmental Science and Pollution Research, 2022)

Genetic and environmental influence on foliar carbon isotope composition, nitrogen availability and fruit yield of 5-year-old mango plantation in tropical Australia - Weiling Sun; Zhihong Xu; Paula Ibell; Ian Bally (Journal of Soils and Sediments, 2021)

Polybrominated diphenyl ethers (PBDEs) in the Danjiangkou Reservoir, China: identification of priority PBDE congeners - Yaomin Luo; Wanzi Shi; Mingtao You; Ruijie Zhang; Si Li; Nan Xu; Weiling Sun (Environmental Science and Pollution Research, 2021)

Spatiotemporal distribution, risk assessment and source appointment of metal(loid)s in water and sediments of Danjiangkou Reservoir, China - Tong Zheng; Chenyuan Dang; Sining Zhong; Weiling Sun; Qian Chen (Environmental Geochemistry and Health, 2021)

Simulating compound flooding events in a hurricane - Yinglong J. Zhang; Fei Ye; Haocheng Yu; Weiling Sun; Saeed Moghimi; Edward Myers; Karinna Nunez; Ruoyin Zhang; Harry Wang; Aron Roland; Jiabi Du; Zhuo Liu (Ocean Dynamics, 2020)

Occurrence and distribution of antibiotic resistance genes in the sediments of drinking water sources, urban rivers, and coastal areas in Zhuhai, China - Aolin Li; Lujun Chen; Yan Zhang; Yile Tao; Hui Xie; Si Li; Weiling Sun; Jianguo Pan; Zhidong He; Chaoan Mai; Yingying Fan; Huanchao Xian; et al. (Environmental Science and Pollution Research, 2018)

Specific effects of prenatal DEHP exposure on neuroendocrine gene expression in the developing hypothalamus of male rats - Na Gao; Ruixia Hu; Yujing Huang; Long Dao; Caifeng Zhang; Yongzhe Liu; Lina Wu; Xutong Wang; Weiling Yin; Andrea C. Gore; Zengrong Sun (Archives of Toxicology, 2018)

Migration of endophytic diazotroph Azorhizobium caulinodans ORS571 inside wheat (Triticum aestivum L) and its effect on microRNAs - Li Qiu; Qiang Li; Junbiao Zhang; Yongchao Chen; Xiaojun Lin; Chao Sun; Weiling Wang; Huawei Liu; Baohong Zhang (Functional & Integrative Genomics, 2017)

Evaluation of a high-resolution historical simulation over China: climatology and extremes - Entao Yu; Jianqi Sun; Huopo Chen; Weiling Xiang (Climate Dynamics, 2015)

Adsorption of three selected endocrine disrupting chemicals by aquatic colloids and sediments in single and binary systems - Weiling Sun; Kun Zhou (Journal of Soils and Sediments, 2015)

Trace metals in sediments and aquatic plants from the Xiangjiang River, China - Weiling Sun; Leixin Sang; Bofeng Jiang (Journal of Soils and Sediments, 2012)

Production of diosgenin from yellow ginger (Dioscorea zingiberensis C. H. Wright) saponins by commercial cellulase - Wei Liu; Wen Huang; WeiLing Sun; YuLing Zhu; JinRen Ni (World Journal of Microbiology and Biotechnology, 2010)

Effects of Copper on the Sorption of Phthalate Esters to Yellow River Sediment - Nan Xu; Jinren Ni; Weiling Sun (Water, Air, & Soil Pollution, 2007)

Applicability of the Langmuir equation to copper sorption by loess with high carbonate content - Ni Jinren; Sun Weiling (Hydrobiologia, 2003)

Chemical equilibrium modeling of copper precipitation in a hyper-concentrated solid-liquid system - Xu Nan; Sun Weiling; Ni Jinren (Hydrobiologia, 2003)